Pola Komunikasi Pembelajaran Guru dan Siswa Group Nusa Oktav Orkestra SMA NU 1 Gresik - Fahmi Prastyo Utomo; Nurtyasih Wibawanti Ratna Amina (DIGICOM : Jurnal Komunikasi dan Media, 2022)
In the world of education, teachers and students are involved in the communication process. The communication process can occur in the classroom or outside the classroom. Combining learning methods with effective communication patterns is needed so that knowledge can be accepted and understood by students. The research entitled Effectiveness of Communication Between Teachers and Students in Group Learning Nusa Oktave Orchestra SMA NU 1 Gresik was motivated by the researcher's curiosity about the effectiveness of communication between teachers and students in learning in groups. The purpose of this study was to determine the effectiveness of communication between teachers and students in learning in groups. This research is a type of qualitative-descriptive research, the researcher conducts interviews with key informants and informants. This study refers to Lasswell's theory combined with the s-r (stimulus-response) model. To measure the effectiveness of communication, the researcher used the communication effectiveness indicators of Stewart L. Tubbs and Sylvia Moss, namely understanding, pleasure, influencing, social relations and action. Through research that has been carried out by researchers, communication between teachers and students in group learning Nusa Oktav Orchestra SMA NU 1 Gresik is effective. Both teachers and students can understand each other's material, have fun in the activity, can have a good influence, and students develop and learn according to the expectations and directions of the teacher.